MODEL PEMBELAJARAN BERBASIS WEB E-LEARNING DALAM MENGHADAPI COVID-19 - Henni Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
Education has a broad enough meaning, education can be interpreted as an effort to educate the nation, instill moral and religious values ​​and others. The role of education is greater, because of its position as an adult. Therefore, the wheels of education must be in line with developments in information and communication technology that have developed along with the development of globalization. The development of technology and information is very rapid, especially the development of the internet helped encourage the development of distance learning concepts. Distance education is due to the Covid-19 pandemic situation that is endemic in the world, especially in Indonesia. The cause of the spread of the Corona virus in various countries makes us see the reality that the world is changing, changes in the fields of technology, economics, politics to education in the midst of crisis due to Covid-19. These changes require us to prepare ourselves and always learn. Therefore, the challenges we have to face online learning, with one of the web-based learning models (e-learning) makes it easy to interact between educators and good students, in the form of Real Time (Chat Room) and online learning meetings must be part of all learning so that the quality of education is improved.